Reading Music through Literary Scholarship: Granville Bantock, Shelley, and The Witch of Atlas. Issue 1 (2nd January 2017) - Allis, Michael
ABSTRACT: James Hepokoski's contractual definition of program music, presented in his 1992 chapter on Richard Strauss's Don Juan, can be further developed through a discussion focused upon Granville Bantock's 1902 orchestral poem, The Witch of Atlas, based on a poem by Percy Bysshe Shelley of 1820. While Bantock's expurgated paratext in his published score is significant, meaningful interpretive strategies for his orchestral refiguring of Shelley's poem are to be found in the realm of literary scholarship: specifically, issues relating to the genre of mythopoesis, the concept of transformation, and Shelley's awareness of the visual. The distinctive structure of Bantock's The Witch of Atlas can also be contextualized in terms of Bantock's pre-war orchestral refigurings of other literary texts. In all these works, Bantock's structural decisions can be seen as a direct representation of the literary models upon which they are based; not only does this suggest parallels with Strauss, but it helps us to reassess Bantock's status in relation to the more familiar composers associated with the "first, active phase" of musical modernism.